Connect with a global community of experts on IDNLearn.com. Get prompt and accurate answers to your questions from our community of experts who are always ready to help.
Answer
(3x² + x - 2) (-4x² - 2x - 1) = -12x⁴ - 10x³ + 3x² + 3x + 2
Explanation
To expand this, we will use one of the two expressions to open the other one.
(3x² + x - 2) (-4x² - 2x - 1)
= 3x² (-4x² - 2x - 1) + x (-4x² - 2x - 1) - 2 (-4x² - 2x - 1)
= -12x⁴ - 6x³ - 3x² - 4x³ - 2x² - x + 8x² + 4x + 2
= -12x⁴ - 6x³ - 4x³ - 3x² - 2x² + 8x² - x + 4x + 2
= -12x⁴ - 10x³ + 3x² + 3x + 2
Hope this Helps!!!